Students’ Attitude Toward Character Building Courses at Bina Nusantara University - Benny, Benny; Hermawati, Oki; Mustikasiwi, Anggaripeni; Djap, Wylen; Irawan, Dadang (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2021)
Character development is required for students so they can bring benefits to society in the future. Character development in Bina Nusantara University has been carried out since 2001. Character development is in the form of 3 compulsory classes using values from Pancasila, Citizenship, and Religion. To improve continuously, it is necessary to find out students' attitudes toward character-building courses they had taken. This research measures students' attitudes towards the importance of character development, their favorite character-building course, how character-building courses influence their character, and whether applicable and relevant to everyday life. The result of the research shows students understood the importance of character development, the Character Building: Religion course was their favorite. The Character Building: Religion highly affects their character and is very applicable and relevant. Character Building: Pancasila and Character Building: Civics has an influence on their character, which are also applicable and relevant. The current state of Character-Building courses is good but still has room to improve. By knowing how students respond, further improvement can be more precise and effective.